2019
DOI: 10.28933/ojgh-2019-08-0205
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease and amebiasis

Abstract: Amebiasis affects around 500 million people in the world. Clinical manifestations of intestinal amebiasis can overlap with symptoms of the inflammatory bowel disease (IBD). Many studies evaluated the relationship of IBD patients during exacerbation periods and amoebic colitis as it is important to rule out the infection before starting steroids and/or immunosuppressive treatment. This mini-review focused on the best strategy to diagnose the infection in this specific population, using classical stool analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…This relationship is supported by studies that found that immunosuppression caused by diabetes was observed in more than 50% of patients with amoebiasis, reinforcing the need for the diagnosis of T2DM in endemic areas to guide therapeutic management in those infected. 55,56…”
Section: Metabolic and Parasitic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship is supported by studies that found that immunosuppression caused by diabetes was observed in more than 50% of patients with amoebiasis, reinforcing the need for the diagnosis of T2DM in endemic areas to guide therapeutic management in those infected. 55,56…”
Section: Metabolic and Parasitic Diseasesmentioning
confidence: 99%
“…This relationship is supported by studies that found that immunosuppression caused by diabetes was observed in more than 50% of patients with amoebiasis, reinforcing the need for the diagnosis of T2DM in endemic areas to guide therapeutic management in those infected. 55,56 Evidence of the mechanism of action of T. cruzi infection under obesogenic and DM conditions has already been documented. A cross-sectional observational study evaluated 361 individuals with an overall mean age of 60.7 years who presented with chronic CD and had migrated from rural to urban centers.…”
Section: Metabolic Diseases Associated With Protozoan Infectionsmentioning
confidence: 99%